^{3}√-x-2
You are being very unclear about what you mean. Give the question in full and show what you tried already. I can only guess you are talking about a Fourier transform or a Laplace transform but you probably mean something entirely different because this is in Pre-University.
So going from $\displaystyle \sqrt{x}$ to $\displaystyle \sqrt[3]{x- 2}$?
Going from x to x- 2 is a shift along the x-axis to the right, two places (x- 2= 0 when x= 2 so what used to be x= 0 has shifted to x= 2).
I'm not sure I would consider going from $\displaystyle \sqrt{x}$ to $\displaystyle \sqrt[3]{x}$ a "functional transformation" in the usual sense of these problems (If it were $\displaystyle 3\sqrt{x}$, that would be a "stretch" by 3 times in the y direction) but it is, of course y to the 2/3 power: $\displaystyle \left(\sqrt{x}\right)^{2/3}= \left(x^{1/2}\right)^{2/3}= x^{1/3}= \sqrt[3]{x}$.